Detection of gastrointestinal protozoa in pet cats presented to selected veterinary clinics in the Klang Valley and risk factors associated with infection - Tan, Li Ping (2016)
The common gastrointestinal protozoa in cats that cause diarrhea are Giardia spp., Isospora spp.and Cryptosporidium spp., and recently Tritrichomonas foetus has been recognized as an emerging protozoa that causes chronic diarrhea in cats. Tritrichomonas foetus infection in cats has not yet been reported in Malaysia. Entamoeba spp. is found rarely but present in cats. This study aimed to investigate the prevalence of gastrointestinal protozoa in pet cats presented to selected veterinary clinics in Klang Valley as well as the risk factors associated with these protozoal infections. Rectal swabs were performed on 30 diarrheic cats presented to selected veterinary clinics in the Klang Valley to culture Tritrichomonas foetus. Another 30 fecal samples were collected randomly and subjected to staining for the detection of other gastrointestinal protozoa. Two out of 30 culture samples were positive for Tritrichomonas foetus with a prevalence of 6.7% and both positive samples were from young kittens. Cryptosporidium spp. was the only protozoa detected in 3 out of 30 samples through the staining method with a prevalence of 10%. This study detected Tritrichomonas foetus for the first time in the Malaysian cat population. The overall prevalence of gastrointestinal protozoa in pet cats in the Klang Valley was low.